Pendampingan Pemberdayaan UMKM Kuliner Berbasis Ekonomi Sirkular Melalui Pengolahan Limbah Menuju Zero Waste Pada UMKM Sukses Bersama Mantap Jambi - Mubyarto, Novi; Erliyana, Nova; Ismadharliani, Aztyara; Martaliah, Nurfitri; Anggraini, Dessy; Syafitri, Nesya (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This Community Service Program (PKM) aimed to strengthen the capacity of UMKM Sukses Bersama Mantap Jambi in implementing circular economy–based waste management toward a zero-waste approach. The program employed a Participatory Action Research (PAR) method involving problem identification, collaborative planning, implementation, and participatory evaluation with MSME actors and environmental stakeholders. Activities were conducted through socialization, training, and hands-on practice focusing on waste identification, processing organic waste into compost and eco-enzyme, and utilizing inorganic waste into value-added products. The results indicate increased knowledge and practical skills of MSME actors in waste management, a reduction of organic waste volume by approximately 20–30%, and the emergence of recycled products with economic potential. This program contributes to the adoption of cleaner, more efficient, and environmentally sustainable business practices and demonstrates the potential for replication in other culinary MSMEs.